2022
DOI: 10.1111/jen.13025
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic conditions drive summer flight phenology of Platypus cylindrus in managed cork oak stands

Abstract: The oak pinhole borer, Platypus cylindrus F., mainly colonizes oaks (Quercus sp.), and it is considered among the most serious pests of cork oak (Quercus suber L.). Despite being traditionally considered as a secondary pest in thermophilic oak woodlands, outbreaks seem to be more frequent throughout the Mediterranean Basin thus becoming a growing forest health concern. In the Iberian Peninsula, this insect mainly attacks cork oaks (Q. suber) causing intense stress to mature trees specially after cork harvestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…6,7 On the other hand, in our study area, fungal prevalence was noticeable earlier than reported by Panzavolta et al 27 who isolated D. corticola more frequently from August to October after an intense drought. In addition, the relative maxima of spore load resulted in unpaired OPB dynamics since peaks of emerging adults occurred from early to mid-June and in mid-July, 13 when expected spore load was lower. These observations evidence the lack of knowledge about the lifecycle of the organisms involved in this pathosystem, encouraging development of future studies focused on sporulation ecology and its relationship with carrier insects' dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 On the other hand, in our study area, fungal prevalence was noticeable earlier than reported by Panzavolta et al 27 who isolated D. corticola more frequently from August to October after an intense drought. In addition, the relative maxima of spore load resulted in unpaired OPB dynamics since peaks of emerging adults occurred from early to mid-June and in mid-July, 13 when expected spore load was lower. These observations evidence the lack of knowledge about the lifecycle of the organisms involved in this pathosystem, encouraging development of future studies focused on sporulation ecology and its relationship with carrier insects' dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Six sampling plots were set in Catalonia (North‐eastern Spain) in managed mature cork oak stands between April and October 2021 (Table 1) for monitoring P. cylindrus summer flight period 13 . We established this study in the county of La Selva (Girona, Spain) in the core area of the NE Spain cork production region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, approximately 30% of potential crop yields are lost each year due to pests, weeds, and agricultural diseases 1–3 . Indeed, in the Mediterranean area, an important number of pests can colonize cork oaks ( Quercus suber L ), causing intense stress to mature trees, especially after the cork harvesting season 4–7 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Indeed, in the Mediterranean area, an important number of pests can colonize cork oaks (Quercus suber L), causing intense stress to mature trees, especially after the cork harvesting season. [4][5][6][7] Mediterranean cork oak forests are one of the world's most interesting biodiversity hotspots, cork oak forests, and woodlands cover a large area approximately 2.2 million hectares across the central and western part of the Mediterranean Basin and North Africa, in Morocco, Algeria, and Tunisia, and are mainly exploited for cork extraction, with management systems that vary from semi-natural to pastoral. 8,9 The decline of cork oak trees is a prevalent issue across their entire distribution range and is primarily caused by poor management and unfavorable weather conditions.…”
Section: Introductionmentioning
confidence: 99%